Proposed vector candidate: Leptotrombidium palpale for Shimokoshi type Orientia tsutsugamushi. (12th February 2013) - Seto, Junji; Suzuki, Yu; Otani, Katsumi; Qiu, Yongjin; Nakao, Ryo; Sugimoto, Chihiro; Abiko, Chieko
Abstract To identify the vector species for Shimokoshi type Orientia tsutsugamushi, a survey of larval trombiculid mites was conducted in Yamagata Prefecture, Japan from April to May 2012. In all, 2889 larval trombiculid mites were obtained from 21 Apodemus speciosus rodent hosts, 2600 of which were morphologically classified into eight species in three genera. After screening of O. tsutsugamushi DNA in individual larval trombiculid mites using real‐time PCR targeting the 16S ribosomal RNA gene, serotype‐specific nested PCRs targeting the 56 kDa protein gene were performed, followed by sequencing analysis. As a result, Shimokoshi type O. tsutsugamushi DNA was identified from 3 (1.9%) of 157 Leptotrombidium palpale. This is the first study to identify Shimokoshi type O. tsutsugamushi DNA in L. palpale. The results indicate that L. palpale is a possible vector for Shimokoshi type O. tsutsugamushi.